2017
DOI: 10.1016/j.addr.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Transflammation: Innate immune signaling in nuclear reprogramming

Abstract: Induction of pluripotency in somatic cells by retroviral overexpression of four transcription factors has revolutionized the field of stem cell biology and regenerative medicine. The efficient induction of pluripotency requires the activation of innate immune signaling in a process termed “transflammation” [1]. Specifically, the stimulation of pattern recognition receptors (PRRs) causes global alterations in the expression and activity of epigenetic modifiers to favor an open chromatin configuration. Activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 139 publications
(177 reference statements)
0
7
0
Order By: Relevance
“…More recently, Qadir et al found a robust connection between death receptor CD95/FAS, Type I IFN-dependent phosphorylation of STAT1 and stemness in human breast cancer and squamous carcinoma cell lines, which can, in part, explain the correlation between STAT1 activation and therapy resistance observed in these cancer cells [ 235 ]. Remarkably, the stimulation of TLR3 and RIG-I induces in somatic cells an innate epigenetic signature which is associated to a process known as “transflammation” [ 236 ], involving chromatin remodeling and subsequent nuclear reprogramming, cell plasticity, pluripotency, and even malignant transformation [ 237 , 238 ]. In line with these data, experiments in breast cancer cells put in evidence that activation of NF-κB and β-catenin signaling downstream of TLR3 promoted the enrichment of a subset of cells with a CSC-like phenotype [ 239 ].…”
Section: Type I Ifns and Cancer: A Troubled Relationshipmentioning
confidence: 99%
“…More recently, Qadir et al found a robust connection between death receptor CD95/FAS, Type I IFN-dependent phosphorylation of STAT1 and stemness in human breast cancer and squamous carcinoma cell lines, which can, in part, explain the correlation between STAT1 activation and therapy resistance observed in these cancer cells [ 235 ]. Remarkably, the stimulation of TLR3 and RIG-I induces in somatic cells an innate epigenetic signature which is associated to a process known as “transflammation” [ 236 ], involving chromatin remodeling and subsequent nuclear reprogramming, cell plasticity, pluripotency, and even malignant transformation [ 237 , 238 ]. In line with these data, experiments in breast cancer cells put in evidence that activation of NF-κB and β-catenin signaling downstream of TLR3 promoted the enrichment of a subset of cells with a CSC-like phenotype [ 239 ].…”
Section: Type I Ifns and Cancer: A Troubled Relationshipmentioning
confidence: 99%
“… 29 Similar results were then obtained with reprogramming to endothelial cells. 30 It was subsequently demonstrated that Rig-I, IRF3, and NF-κB were necessary for the effects that the authors had observed. 31 Considering the role of IRF3 and NF-κB, it is interesting to speculate that ICR2 may also enhance reprogramming based methods of iPSC and endothelial cell generation.…”
Section: Discussionmentioning
confidence: 97%
“…Reprogramming fibroblasts to iPSCs and endothelial cells has also been shown to be dependent upon RNA-sensing receptor pathways. 29 , 30 Conversion of fibroblasts into induced pluripotent stem cells (iPSCs) is efficient when the reprogramming factors Oct4, Sox2, Klf4, and c-Myc are delivered into fibroblasts via viruses. In contrast, expression of the reprogramming factors via cell permeable peptides is very inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that adjuvants can promote maturation of DCs and upregulate the expression of costimulating molecules on the DCs such as CD80 and CD86, which can provide a secondary signal for activation of naive T cells (35,47). In particular, I-IFNs secreted from TLRs, retinoic acid-inducible gene-I-like receptors (RLRs), and STING pathway can promote the maturation of DCs and enhance immune responses (21,(48)(49)(50). Compared to TLR or RLR agonists, STING agonists have superior safety, inducing relatively low levels of local and systemic inflammation.…”
Section: Fig 5 Effect Of Ic8/mn Lnps On Maturation and Antigen Presen...mentioning
confidence: 99%